2021
DOI: 10.1101/2021.03.28.437369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preliminary report on SARS-CoV-2 Spike mutation T478K

Abstract: Several SARS-CoV-2 variants have emerged, posing a renewed threat to COVID-19 containment and to vaccine and drug efficacy. In this study, we analyzed more than 820,000 SARS-CoV-2 genomic sequences deposited up to March 26, 2021 and identified a novel T478K mutation located on the SARS-CoV-2 Spike protein. The mutation is structurally located in the region of interaction with human receptor ACE2 and was detected in 4,214 distinct cases. We show that T478K has appeared and risen in frequency since January 2021,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…On the other hand, 20B/T478K.V1 can be undoubtedly classified as a VOI, with all the potential elements to become a VOC in Mexico and worldwide. This has been suggested as well by other authors (Di Giacomo et al 2021;, which report the occurrence of this variant in Mexico, USA and Europe, with an emphasis in mutations T478K and P681H.…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, 20B/T478K.V1 can be undoubtedly classified as a VOI, with all the potential elements to become a VOC in Mexico and worldwide. This has been suggested as well by other authors (Di Giacomo et al 2021;, which report the occurrence of this variant in Mexico, USA and Europe, with an emphasis in mutations T478K and P681H.…”
Section: Discussionsupporting
confidence: 70%
“…The TTTA->T deletion in Spike protein is predicted to change the structure of the N3 NTD loop (amino acid positions 140-156) and has been shown to impact neutralization by a variety of neutralizing antibodies (33). T478K affects the Spike binding domain with the human receptor ACE2, raising the electrostatic potential at the interface and may represent a genetic pathway for SARS-CoV-2 to avoid immune detection (34). N501Y is one of six essential amino acids involved in the development of the RBD-hACE2 complex.…”
Section: Positionmentioning
confidence: 99%
“…T478K is also located in RBD, and in silico analysis of spike structure has predicted that T478K may alter the electrostatic surface and increase steric hindrance of the S protein (Di Giacomo et al, 2021). It is suggested that T478K could enhance the binding affinity of RBD to ACE2.…”
Section: Discussionmentioning
confidence: 99%